Deciphering the virulent Vibrio harveyi causing spoilage in muscle of aquatic crustacean Litopenaeus vannamei - Lian Gan; Jianwei Zheng; Wei-Hua Xu; Jianhao Lin; Jingshu Liu; Yu Zhang; Zizhan Wu; Zhaolin Lv; Youming Jia; Qingqi Guo; Shijun Chen; Chuanhe Liu; et al. (Scientific Reports, 2022)
Abstract The muscle of aquatic crustaceans is perishable and susceptible to environmental contamination. Vibrio harveyi is a widely occurring pathogen in aquatic animals. Here, bath treatment with a virulent V. harveyi strain (which was added directly in the rearing water to imitate environmental contamination) isolated from the muscle of the whiteleg shrimp, Litopenaeus vannamei, caused the muscle of Li. vannamei to display a whitish-opaque appearance due to microscopic changes including muscle lysis, muscle fiber damage and microbial colonization. When administered orally by incorporating this isolate in feed (which is an imitation of infection via natural route), rather than direct invasion followed by colonization in the muscle, this isolate indirectly stimulated severe muscle necrosis in Li. vannamei via steering the enrichment of two important (human) pathogens, V. cholerae and V. vulnificus, and one environmental bacterium Pseudomonas oleovorans, based on the meta-taxonomic analyses. In addition to the scientifically proven viral diseases, our research proved that bacterial agents are also capable of causing muscle spoilage in crustaceans via changing the microbial composition, and that the crustaceans might be exploited as the wide-spectrum sensitive bio-detector to indicate the extent of microbial contamination.